The blossoming of militancy's hope: The Dona Zizi Committee in the life of rural women from Mato Grande - RN (TEL Tempo, Espaço e Linguagem, 2023)
This study focuses on social subjects who were systematically suppressed from the production of knowledge and political action with the FOMAG (Collegiate Forum of the Municipalities of Territories of Citizenship) of the TC of Mato Grande/RN and that, thanks to the struggle for the constitution of the Dona Zizi committee, build alternative instruments for a more inclusive policy for women in a field of forces more suited to their participation and interests. Reflecting on how the militancy of community-based rural feminism can bring women who are made invisible in their rights to the political scene. In addition to contributing to the scientific theoretical debate on the importance of territorial approach policies for rural areas, in view of the setbacks of the last four years. It is concluded by the importance of the space created and by the collectively learned strategies that empower them.